Tingkat Peran Kelurga dalam Pengawasan Pasien Halusinasi terhadap Upaya Mengontrol Halusinasi dengan Teknik Menghardik - Kaylatuz Zahra; Wien Soelistyo Adi; Herry Prasetyo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: The role of the family is very important to avoid recurrence. There is an influence of the rebuke technique on the patient's ability to control hallucinations. The family's role is to remind or even teach the patient rebuking techniques at home, so it is necessary to implement family intervention with rebuking techniques to try to control the patient's ability to hallucinate. Objective: This study aims to determine the differences in the level of family role in supervising patients with hallucinations versus efforts to control hallucinations using rebuke techniques. Method: Quasi-experimental research design using pre-posttest without control group. The sample was 88 people, namely the patient's family who took the control patient to the outpatient clinic. The sampling technique used was purposive sampling. The data collection instrument used the dependent t test. Results: The results of the study p value = <0.001 (<0.05) which means There is a significant difference between the level of family role before and after the intervention with the rebuke techniques taught to the patient's family. Meanwhile, p value = <0.001 which this means that there is a significant difference between the patient's ability to control hallucinations before and after intervention with the rebuke techniques taught by the patient's family. Conclusion: There is a significant difference in the level of family role in supervising patients with hallucinations versus efforts to control hallucinations using rebuke techniques.